ANALYSIS OF BAGAN FITTING EQUIPMENT IN THE AMPANG PULAI VILLAGE SUB-DISTRICT KOTO XI TARUSAN, PESISIR SELATAN REGENCY, SUMATERA BARAT PROVINCE - Kurnia Wulan Dari; Hamdi Hamid; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This Research was conducted on April 2019 in The Ampang Pulai Village, Koto XI Tarusan Sub-District, Pesisir Selatan Regency, Sumetera Barat Province. This study aims to analyze the investment in fishing boat fishing gear, analyze the income and profits of fishing boat fishing gear capture business, and analyze the feasibility of Bagan fishing gear business. The method used in this study is a survey method which was analyzed descriptively. The number of respondents in this study was 6 people for the size of the vessel 20 GT and 30 GT. Based on the results of research on the total investment for Bagan fishing gear business with a fishing fleet measuring 20 GT is Rp. 1.408.450.000 .and 30 GT is Rp.1.828.667.500. Based on the calculation of the Net Present Value (NPV) investment criteria, the value of 30 GT is better than the 20 GT vessel( 4.347.288.826>1.681.252.418), which means that IRR> 1 and the Bagan Perahu fishing gear business benefit and deserve to continue. While the Benefit Of Cost Ratio (BCR) of fishing gear business in the BCR value chart obtained from the 20 GT Boat Chart business is 1.25, which means that every cost is Rp. 1 benefit is Rp. 1.25 and the 30 GT Rp.1.82 ship is which means that every cost is Rp. 1 benefit is Rp.1.82. The vessel's IRR of 20 GT is 50.21% and Ship 30 GT is 69.22% (IRR> i), is value is greater than the highest interest rate per year. Keywords: Fisherman, fish gear,business feasibility analysis